While life education matters, how should higher education respond? conceptualizing its integration within academic management - Zhang, Yuanyuan; Siribanpitak, Pruet; Chaemchoy, Sukanya (Edelweiss Applied Science and Technology, 2026)
This study aims to conceptualize and examine how life education can be systematically integrated into academic management within the context of Chinese higher education. Adopting a mixed-methods design, the research first developed a conceptual framework through an extensive review of literature and policy documents, which was subsequently validated by a panel of experts. The framework was then empirically examined using survey data collected from 246 undergraduate students in Jiangsu Province. Descriptive statistical analysis revealed that students demonstrated relatively high levels of development in life values, life responsibilities, self-awareness, life skills, and life safety, whereas mental health emerged as the least developed dimension, exhibiting moderate levels and substantial variability. These findings suggest a structural imbalance in current academic management practices, where value-oriented and normative outcomes are more effectively supported than sustained psychological development. The study concludes that life education outcomes are closely shaped by the degree of coherence across academic management domains, particularly curriculum design, teaching practices, assessment mechanisms, and out-of-classroom learning. Practically, the findings highlight the need for higher education institutions to move beyond fragmented support services and to embed mental health and life education more deliberately into core academic management processes to promote holistic and sustainable student development.